Case Report: Novel molecular characterization of rare primary mucinous adenocarcinoma of the renal pelvis - Taylor, Megan K.; Paster, Irasema C.; Arevalo Salazar, Dory E.; Chipollini, Juan; Recio Boiles, Alejandro (Frontiers in Oncology, 2026)
Mucinous adenocarcinoma of the renal pelvis (MAC-RP) is an exceedingly rare condition, accounting for less than 1% of malignancies originating from this epithelial site. We report a case of MAC-RP in a woman presenting with right flank pain from obstructing stones, recurrent urinary tract infections, and ureteral stents. Imaging showed a right kidney mass consistent with xanthogranulomatous pyelonephritis (XGP) with an abscess surgically removed. Pathology after radical nephrectomy unexpectedly revealed in situ MAC-RP with intestinal metaplasia at the margin. Surveillance testing showed positive levels of CEA, CA19-9, and novel ctDNA and cfDNA despite negative results from pan-endoscopy and imaging. A subsequent monitoring imaging identified a right flank mass that was resected, confirming recurrent MAC-RP. The patient completed 6 months of adjuvant mFOLFOX6, as recommended in the MAC-colon cancer guidelines. The patient completed the treatment without any evidence of measurable molecular or radiological disease. At 4 months after the last systemic therapy, the patient’s biomarkers were rising, matching radiological local, ovarian, and pleural recurrences, which were histologically confirmed. Since there are no established guidelines for MAC-RP, our team is the first to apply cutting-edge cancer technologies to inform future clinical decisions and molecular tumor board discussions and to compare the genomic distance of MAC-RP with that of other bladder or colorectal origin sites.